The Real War - Nixon, Richard (Rawalpinde Army Education Press, 1980)
The former president examines the forces contending for power in today's world, assesses their goals, strategies and relative strengths and weaknesses, and weighs the implications of current trends
Include Index
Keywords: Diplomatic relations -- United States -- World politics